Analisis Efisiensi Pemasaran Produk Wine pada PT. Hatten Bali - BELLA MARISOL MAZARELLO BARU GUTERRES; I NYOMAN GEDE USTRIYANA; NI WAYAN PUTU ARTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Marketing Efficiency Analysis of Wine Product by PT. Hatten Bali This research is aimed to acknowledge the system of the marketing channels and itsfunctions, calculate the margins of the marketing and producer share to alsoanalyzing the efficiency of overall products marketing system of hatten wineproducts by PT. Hatten Bali. The methods of data collection used are observation,interviews, and literatur reference. Methods for data collection in this study, wereobservation, interviews, and literatur reference. The samples using of 30 retailersaround Denpasar City and Badung Regency chosen with snowball sampling. Dataanalyzing by descriptive qualitative and descriptive quantitative. The results showedthat marketing channels of PT. Hatten Bali involving the retailers from hotels, villas,restaurants, and grocery stores. There are two types of marketing channels, type oneis producer-consumer while type two is producer-retailers-consumer. The highestmarketing margin from type two is recorded 181.000 idr per bottle while the lowestmarketing margin coming from type one is 0.000 idr per bottle. The highestproducer’s share is on type one by 100% and the lowest is on type two by 43.92%.The highest price efficiency is on type two by 222.73% and the lowest is on type oneby 100%. The highest operational efficiency is on type two by 9.279,20% and thelowest recorded is on type one by 3.917,81%. Type one of marketing channels is themost efficient channel based on the analysis of margin marketing, produsen sharesand price efficiency. While type two is the most efficient channel of marketing basedon its operational efficiency analysis.